La Explanatio in Cantica Canticorum de Justo de Urgel. Una reconsideración - Cano Herrero, Emmanuel (Augustinianum, 2024)
In contrast to other opinions, this article offers a new reading key to Justus of Urgell’s Explanatio in Cantica Canticorum. The analysis of the text in its historical context presents the Spanish bishop’s commentary as a response to Priscillianism and Arianism, two heresies still active in the Iberian Peninsula in the first half of the 6th century. From a context of oriental influence in Visigothic Spain at the time, the author offers a theology of deification in line with other writers such as Irenaeus and Origen against Gnosticism, or Athanasius and Gregory of Nyssa against Arianism. Furthermore, the relation with the bishop of Lyon is particularly evidenced from a common salus carnis theology in opposition to the gnostic challange.